Ghost town at sundown - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1997)
Their magic tree house takes Jack and Annie back to the Wild West, where they experience excitement and danger and try to solve a riddle.
"A Stepping Stone book.".
L.A. Recommended Foreign Language.
3.4
3-6
Keywords: Annie (Fictitious character : Osborne) -- Juvenile fiction; Frontier and pioneer life -- West (U.S.) -- Juvenile fiction; Jack (Fictitious character : Osborne) -- Juvenile fiction; Magic -- Juvenile fiction; Time travel -- Juvenile fiction; Tree houses -- Juvenile fiction; Annie (Fictitious character : Osborne) -- Fiction; Frontier and pioneer life -- West (U.S.) -- Fiction; Jack (Fictitious character : Osborne) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Annie (Fictional character : Osborne) -- Fiction; Frontier and pioneer life -- West (U.S.) -- Fiction; Jack (Fictional character : Osborne) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Western stories; West (U.S.) -- Fiction